Trabalhadores e periféricos: identidades em (des)construção nas periferias de São Paulo - Leonardo Fontes (e-cadernos ces)
This article analyzes the formation and transformations in the identities of São Paulo’s peripheries dwellers in recent decades. Our proposal here is that identity must be understood in a relational and historical way. Thus, it is sewn together with discourses, practices, and processes that produce subjectivities. The paper is based on an ethnographic work carried out in two neighborhoods on the outskirts of São Paulo. It is argued that, in the 1970s and 1980s, the identity of “workers” was formed in contrast to that of “bosses” and “bandits”. This identity was the basis of a collective project to integrate workers into the wage society and the world of citizenship rights. After the productive restructuring and social changes in the 1990s and 2000s, this identity disintegrated and gave way to the identity of “peripherals”. This new identity was built in cultural mobilization around cultural movements and collectives in opposition to the “elites” and in response to the stigma that these regions suffer from.